“A very strong stream it is”: An Interpretation of Yoiks about the Gievdneguoika Waterfall - Basa, Violeta (Studia Scandinavica, 2023)
This article is devoted to yoik, the traditional vocal music of the Sámi people. It explains what yoiks are and what meaning they have in Sámi culture as an expression of remembrance and emotions. The study analyses the lyrics of three yoiks about a waterfall on the Kautokeino river called Gievdneguoika, and examines how they express emotions. It also considers what these yoiks and the literary techniques they rely on say about the cultural values and attitudes of the Sámi people. This article is devoted to yoik, the traditional vocal music of the Sámi people. It explains what yoiks are and what meaning they have in Sámi culture as an expression of remembrance and emotions. The study analyses the lyrics of three yoiks about a waterfall on the Kautokeino river called Gievdneguoika, and examines how they express emotions. It also considers what these yoiks and the literary techniques they rely on say about the cultural values and attitudes of the Sámi people. This article is devoted to yoik, the traditional vocal music of the Sámi people. It explains what yoiks are and what meaning they have in Sámi culture as an expression of remembrance and emotions. The study analyses the lyrics of three yoiks about a waterfall on the Kautokeino river called Gievdneguoika, and examines how they express emotions. It also considers what these yoiks and the literary techniques they rely on say about the cultural values and attitudes of the Sámi people. This article is devoted to yoik, the traditional vocal music of the Sámi people. It explains what yoiks are and what meaning they have in Sámi culture as an expression of remembrance and emotions. The study analyses the lyrics of three yoiks about a waterfall on the Kautokeino river called Gievdneguoika, and examines how they express emotions. It also considers what these yoiks and the literary techniques they rely on say about the cultural values and attitudes of the Sámi people.